Integrated evaluation of hemodynamics: a novel approach for the assessment and management of preterm infants with compromised systemic circulation. (October 2018) - Elsayed, Yasser; Louis, Deepak; Ali, Yaser; Amer, Reem; Seshia, Mary; McNamara, Patrick
Abstract Objective To establish normal reference values for tissue oxygen delivery and consumption in preterm infants and demonstrate the usefulness of the integrated evaluation of hemodynamics (IEH) in preterm infants with compromised systemic circulation (CSC). Methods This study included 32 stable preterm infants and 6 infants (selected cases) who underwent IEH. IEH is a multimodal approach which integrates clinical parameters: data obtained from near-infrared spectroscopy (NIRS) and targeted neonatal echocardiography (TNE). Results Thirty-two hemodynamically stable preterm infants underwent 57 IEH studies. The mean (10th and 90th percentiles) were 0.23 (0.14 and 0.29) for cerebral fractional oxygen extraction (crFOE), 0.2 (0.13 and 0.24) for renal fractional oxygen extraction (rnFOE), and 0.22 (0.19 and 0.27) for mesenteric fractional oxygen extraction (msFOE). The time to full clinical recovery in all sick infants after the change of management was between 4 and 48 h. Conclusion IEH was useful in targeting the management of preterm infants with CSC.